Recent advances in ground anchor and ground reinforcement technology with reference to the development of the art - Barley, A.; Windsor, Christopher (2018)
© 2018 ISRM International Symposium 2000, IS 2000. All rights reserved. The recent advances in ground anchor technology and the related techniques of cable bolting and rock bolting are reviewed. Collectively the technology associated with the three techniques enable design engineers to address stability problems over a range of scales and in a range of geomechanical environments. The techniques have similar aims but have developed into separate disciplines with unique attributes. The procedures for designing and creating ground anchors that meet the stringent requirements associated with modern civil infrastructure are discussed. This contrasts the very different design approaches being developed in rock bolting and cable bolting where standards are less exacting but the design problems can sometimes be more complex.